Penerapan Media Komputer Untuk Meningkatkan Kualitas Pembelajaran PKn - Mersinataria Harefa (JURNAL GLOBAL EDUKASI, 2020)
Abstract: This study aims to improve the learning outcomes of Civics in Class III-A students at SD Negeri 070981 Fodo through computer media. The research subjects were students of Class III-A Public Elementary School 070981 Fodo with 30 students, consisting of 18 male students and 12 female students. The results of this study indicate the average learning outcomes obtained in Civics learning through computer media, namely cycle I 68, cycle II 76. While the percentage of individual completeness obtained in each cycle is 60% cycle I, 87% cycle II. While the average results of student activity in the first cycle 58% with sufficient criteria, and the second cycle 83% with good criteria. The average score of teacher activity in the first cycle 69% with sufficient criteria, second cycle 73% with good criteria. The use of computer media can be used as a reference for the implementation of other learning Keywords: computer media, thematic Abstrak: Penelitian ini bertujuan meningkatkan  hasil  belajar  PKn siswa  Kelas III-A di SD Negeri 070981 Fodo melalui media komputer. Subyek  penelitian  adalah  siswa  Kelas III-A  SD Negeri 070981 Fodo  yang  banyaknya  30  siswa, terdiri  dari    siswa  laki-laki  18  anak  dan  siswa  perempuan  12  anak.  Hasil penelitian ini menunjukkan rata-rata hasil belajar yang diperoleh pada pembelajaran PKn melalui media komputer yakni siklus I 68, Siklus II 76. Sedangkan  persentase  ketuntasan  individual  yang  diperoleh  pada  setiap  siklus  adalah siklus I 60%, siklus II 87%. Sedangkan Hasil rata-rata aktivitas siswa pada siklus I 58% dengan kriteria cukup, dan siklus II 83%   dengan kriteria baik. Rata-rata skor aktivitas guru pada siklus I 69% dengan kriteria cukup, siklus II 73% dengan kriteria baik. Pengunaan media komputer dapat digunakan sebagai acuan untuk pelaksanaan pembalajaran yang lainnya Kata kunci: media komputer, tematik